Adat Pembagian Hewan Kurban dalam Tradisi Islam (Studi Kasus di Kecamatan Siompu Kabupaten Buton Selatan) - Muhammad Shiddiq Abdillah; Iskandar Iskandar; Azman Azman (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2022)
This study aims to explore the Islamic legal perspective on the tradition of distributing sacrificial meat within Islamic traditions (Case Study in Siompu District, South Buton Regency). This research employs a qualitative approach in the form of field research. The findings of this study reveal several points. First, the custom of distributing sacrificial meat in the Siompu District varies by village. Some villages in Siompu District distribute ready-to-eat meat, while others distribute raw meat to the poor. However, many of the poor are unable to process the raw meat, resulting in them selling it at the market price. Second, the study found that some villages set aside a portion of the sacrificial meat to be cooked first and then shared in a communal meal. Second, from an Islamic legal perspective, the practices of distributing sacrificial meat in Siompu District align with the views of Islamic scholars.